Examining Heavy Metal Concentrations in Hair of South African Vervet Monkeys (Chlorocebus pygerythrus) to Access Anthropogenic Impact - Lewis, Alycia E. (East Carolina University, 2017)
High concentrations of heavy metals are known to have deleterious effects on the nervous, endocrine, hepatic, and immune systems of mammals. Environmental toxicology has traditionally been used to understand impacts of pollutants on human health and aquatic and marine ecosystems but has rarely been adopted by primatologists to examine the effects of toxins on nonhuman primates. I analyzed 60 vervet monkey (Chlorocebus pygerythrus) hair samples for concentrations of Arsenic (As), Cadmium (Cd), Lead (Pb), and Mercury (Hg) using an inductively coupled plasma mass spectrometer (ICP-MS). Hair samples were collected from anesthetized monkeys at 10 South African field sites with varying degrees of anthropogenic impact. All hair samples contained Pb and As. Some samples had Cd and Hg but at levels below the limit of quantitation (LOQ). Animals acquire heavy metals naturally via environmental particulates, or through the consumption of food and water and sometimes in unnaturally high quantities as a result of human activity. In South Africa, mining is fairly widespread with the harmful potential for exposure to increased levels of heavy metal pollution. Given our shared physiologies, nonhuman primates can act as proxies for those humans occupying polluted ecosystems, and the data collected from examining nonhuman primate hair for pollutants may also be viewed as less controversial by public and private institutions. The data presented here demonstrate that toxicology studies can improve our understanding of nonhuman primate health and behavior especially for populations in degraded habitats.
Keywords: Old World Monkey; Hair; Anthropogenic Disturbance; Cercopithecus aethiops--Effect of heavy metals on; Environmental toxicology